Dynamical arrest for globular proteins with patchy attractions - Bergman, Maxime J.; Garting, Tommy; De Michele, Cristiano; Schurtenberger, Peter ; 0000-0002-2790-8831; Stradner, Anna (Soft Matter, 2025)
Attempts to use colloid science concepts to better understand the dynamic properties of concentrated or crowded protein solutions are challenging due to the fact that globular proteins generally have heterogeneous surfaces that result in anisotropic or patchy contributions to their interaction potential. This is particularly difficult when targeting non-equilibrium transitions such as glass and gel formation in concentrated protein solutions. Here we report a systematic study of the reduced zero shear viscosity Zr of the globular protein gB-crystallin, an eye lens protein that plays a vital role in vision-related phenomena such as cataract formation or presbyopia, and compare the results to the existing structural and dynamic data. Combining two different tracer particle-based microrheology methods allows us to precisely locate the line of kinetic arrest within the phase diagram and characterize the functional form of the concentration and temperature dependence of Zr. We show that while our results qualitatively confirm the existing view that this protein can be reasonably well described using a coarse-grained picture of a patchy colloid with short range attractions, there are a number of novel findings that cannot easily be understood with the existing simple colloid models. We demonstrate in particular the complete failure of an extended law of corresponding states for a description of the temperature dependence of the arrest line, and discuss the role that transient clusters play in this context.
Publisher Copyright: © The Royal Society of Chemistry 2025.